Análisis epidemiológico de onicomicosis diagnosticada por laboratorio en pacientes menores de 15 años - Palma D., Carlos; Zemelman D., Viviana; Stevens G., Jonathan; Araníbar D., Ligia; Zapata M., Solange; Hernández V., Alicia (Revista Hospital Clínico Universidad de Chile, 2017)
Onychomicosis was considered uncommon in children. During recent years an increase in itsfrequency has been reported in children worldwide. This survey was carried out to estimatethe frequency of causal agents of fungal nail infections in children and adolescents (0-15 yearsof age) during the period 2006-2016 in the Skin Laboratory of Clinical Hospital, Universityof Chile. It was a descriptive, retrospective analysis of all positive culture of children nails. Atotal of 1626 culture was analyzed. Cultures were positive in 417 cases (25,6%). Averageage of patients with positive culture was 9,37 ages. Of the total positive culture, 42,9%was females and 57,1% was males. Toenails were more affected (90,6%) than finger nails.Trichophyton rubrum (66,9%), was the predominant pathogen isolated followed by Candidaspp (26,1%) Trichophyton rubrum + Candida spp (3,8%) Trichophyton mentagrophytes (2,6%)and Trichophyton rubrum + Trichophyton mentagrophytes (0,5%). Fungal fingernail infection byCandida spp. was the most common (66,7%) and Trichophyton rubrum was the most commonin toenail (70,6%). We found a decrease of Candida spp. with age. The results of our study showthat onycomichosis in children and adolescents is not exceptional and should be considered inthe differential diagnosis of nail plate disorder in children.